(untitled) (LIS TODAY, 2021)
The COVID-19 pandemic situation has restrained people at their homes and now a day’s work from home is the new mode of functioning of all offices. Even the Hon’ble Supreme Court has been pleased to issue directives and guidelines for functioning of the Court through Video Conferencing, which will be hereinafter referred to as V.C. and in such case the role of E- Library and its up-gradation and digitalization becomes imminently important for the assistance of, not only the court as well as the but also of the students, research scholars, journalists, etc. The present paper focuses on the importance of e library in the present pandemic situation.